2016
DOI: 10.1038/srep18927
|View full text |Cite
|
Sign up to set email alerts
|

Unique Static Magnetic and Dynamic Electromagnetic Behaviors in Titanium Nitride/Carbon Composites Driven by Defect Engineering

Abstract: Recently, the defect-induced static magnetic behaviours of nanomaterials have been a cutting-edge issue in diluted magnetic semiconductor materials. However, the dynamic magnetic properties of nanomaterials are commonly ignored if their bulk counterparts are non-magnetic. In the present research, titanium nitride-carbon (TiN/C) nanocomposites were found to exhibit both static and dynamic magnetic properties that vary in the opposite trend. Moreover, novel unconventional electromagnetic resonance behaviour was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Unexpected magnetism in dielectric oxide nanostructured materials, even at room temperature, can also be the reason for the formation of a gradient structure [35,36]. The unique magnetism of nanomaterials is usually associated with various structural defects, such as cation vacancies, oxygen vacancies, and structural inhomogeneity, which is confirmed by numerous studies of highly defective magnetic oxides and nitrides [36].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Unexpected magnetism in dielectric oxide nanostructured materials, even at room temperature, can also be the reason for the formation of a gradient structure [35,36]. The unique magnetism of nanomaterials is usually associated with various structural defects, such as cation vacancies, oxygen vacancies, and structural inhomogeneity, which is confirmed by numerous studies of highly defective magnetic oxides and nitrides [36].…”
Section: Introductionmentioning
confidence: 89%
“…However, in recent years, researchers have discovered that nanostructured materials possess unique properties compared to their bulk counterparts, owing to various defects that can influence their physical characteristics. Notably, unexpected magnetism has been observed in dielectric oxide nanostructured materials [35,36,53]. Numerous studies on magnetic oxides and nitrides have demonstrated that their magnetism can be attributed to the structural inhomogeneity of nanopowders and the presence of various defects in their structure, such as cationic and oxygen vacancies [36].…”
Section: Darkly Colored Surface Areamentioning
confidence: 99%
“…2b that the I D /I G of SiCN (MWCNTs) was significantly increased compared with that of SiCN, suggesting that the introduction of MWCNTs brought a great quantity of defects to SiCN (MWCNTs). In the alternating electromagnetic filed, defects can promote polarization loss as polarization centers and thus positively contribute to the attenuation of EMW [2,13].…”
Section: Fig1 Preparation Process Diagram Of Sicn (Mwcnts)mentioning
confidence: 99%
“…have been widely used as wear-and corrosion-resistant coatings, diffusion barriers, gate electrodes in field-effect transistors (FET), as replacement of polycrystalline Si in large-scale integrated circuits, contact layers in solar cells, metal-insulator-superconductor (MIS) tunnel junctions [5] [6] [7] and lowloss plasmonic materials [8]. Furthermore, TiN is known to have a low electromagnetic loss at microwave frequencies and has found applications in low-loss superconducting qubits, microwave resonators for qubits and microwave kinetic inductance detectors [9] [10]. Recently, anomalous defect-induced magnetic and electromagnetic properties have been reported for both as-prepared and Fe-doped TiN nanocrystals [10] [11], although bulk TiN is non-magnetic.…”
Section: Thin Filmsmentioning
confidence: 99%
“…Furthermore, TiN is known to have a low electromagnetic loss at microwave frequencies and has found applications in low-loss superconducting qubits, microwave resonators for qubits and microwave kinetic inductance detectors [9] [10]. Recently, anomalous defect-induced magnetic and electromagnetic properties have been reported for both as-prepared and Fe-doped TiN nanocrystals [10] [11], although bulk TiN is non-magnetic. This renders TiN an appealing material for multi-functional ferromagnetic materials in spintronic applications.…”
Section: Thin Filmsmentioning
confidence: 99%